The Role of Audit Quality in Moderating the Relationship Between Corporate Governance, Ownership Structure, and Earnings Management - Rahmaniar Wulandari; Syarbini Ikhsan; Syarif M Helmi; Muhammad Fahmi; Nina F Dosinta (Poltanesa, 2025)
This study aims to examine the role of audit quality in moderating the relationship between Good Corporate Governance (GCG), ownership structure, and earnings management in banking sector companies listed on the Indonesia Stock Exchange during the period 2019-2023. The method used in this study is quantitative, with data analysis using SPSS 25. The sample used in this study consisted of banking sector companies listed on the Indonesia Stock Exchange, with data obtained from the company's annual report. The results of the study indicate that GCG has a significant effect on earnings management, indicating that good GCG implementation can increase transparency in earnings management. Ownership structure does not have a significant effect on earnings management, indicating that direct control by the owner is not strong enough to influence earnings management in the Indonesian banking sector. Audit quality is proven to moderate the effect of GCG on earnings management, meaning that high audit quality strengthens the relationship between GCG and more transparent earnings management. Audit quality moderates the effect of that good external monitoring can increase the effectiveness of monitoring carried out by owners.